PENGARUH TEMUAN AUDIT, REKOMENDASI HASIL PEMERIKSAAN, DAN UKURAN PEMERINTAHAN DAERAH TERHADAP OPINI AUDIT PADA PEMERINTAH DAERAH DI INDONESIA - Raihania Salsabila; Ickhsanto Wahyudi (AKSELERASI: Jurnal Ilmiah Nasional, 2022)
The purpose of this study was to analyze the effect of audit findings, recommendations on audit results, and the size of local government on audit opinions on local governments in Indonesia. This research uses quantitative research. Population sampling technique is done by using purposive sampling method. To test the hypothesis in this study using the Multinomial Logistics Regression Analysis test. Based on empirical facts and hypothesis testing in this study, it can be concluded that: 1) audit findings do not affect audit opinion on local governments; 2) audit recommendations influence audit opinions on local governments; and 3) the size of the local government influences the audit opinion on the local government.